Blockchain for smart homes: Review of current trends and research challenges. (May 2020) - Moniruzzaman, Md.; Khezr, Seyednima; Yassine, Abdulsalam; Benlamri, Rachid
Abstract: The increasing popularity of smart home applications has introduced unprecedented demand for improving the underlying information technology infrastructure to ensure the transparency, security, and privacy of user data. Blockchain is a promising technology capable of addressing such demand. This paper provides a comprehensive review of current advancements and highlights the major progress of employing blockchain in smart home systems. We first discuss blockchain techniques and the prerequisites of a smart home to adapt blockchain technology. Then, we present various applications of blockchain for smart homes and discuss the most commonly used methods in the literature. We also present two case studies to show how blockchain empowers smart home transactions by eliminating the middleman. This paper also reports on the major challenges pertaining to interoperability protocols, security and privacy, data collection and sharing, data analytics, and latency. Finally, the paper identifies potentially promising areas for future research.